Hepatitis G virus; Structure, epidemiology and clinical significance - (:unkn) unknown (My University, 1998)
Hepatitis G virus is a new member of hepatotropic virus belonging to the family of Flaviviridae. Its genome consists of 2900 amino acids. This new virus which has been identified two years ago is a positive stranded RNA virus and causes both acute and chronic hepatic disease. The structure, epidemiology and clinical importance of hepatitis G virus will be discussed in this article.
Keywords: Hepatitis G virus